Maternal employment and child socio-emotional behaviour in the UK: longitudinal evidence from the UK Millennium Cohort Study. Issue 7 (10th January 2011) - McMunn, Anne; Kelly, Yvonne; Cable, Noriko; Bartley, Mel
Abstract : Background: Mothers of young children are increasingly combining paid work with childrearing. Empirical evidence on the effects of maternal employment on children is contradictory and little work has considered the impact of maternal employment within the context of the employment patterns of both parents. Methods: Data on parental employment across three sweeps (when children were in infancy, age 3 and age 5 y) of the Millennium Cohort Study, a large nationally representative prospective birth cohort study, were used to investigate the relation between parental employment and child socio-emotional behaviour at age 5 years independent of maternal education, maternal depression or household income. The cumulative effect of maternal employment across the early years was investigated. The impact of maternal employment in the first year of life was separately examined as a potentially 'sensitive period'. Results: There was no evidence of detrimental effects of maternal employment in the early years on subsequent child socio-emotional behaviour. There were significant gender differences in the effects of parental employment on behavioural outcomes. The most beneficial working arrangement for both girls and boys was that in which both mothers and fathers were present in the household and in paid work independent of maternal educational attainment and household income. Conclusion: No detrimental effects of maternal employment in the early years were seen. There were important gender differences in relationships between parental working arrangements and child socio-emotional outcomes.